2019
DOI: 10.2147/ijn.s190928
|View full text |Cite
|
Sign up to set email alerts
|

<p>The effects of graphene and mesenchymal stem cells in cutaneous wound healing and their putative action mechanism</p>

Abstract: This study provides a review of the therapeutic potential of graphene dressing scaffolds and mesenchymal stem cells (MSCs) and their synergistic effects with respect to cutaneous wound healing. This study also considers their putative action mechanism based on the antibacterial, immunomodulating, angiogenic, matrix remodeling effects of materials belonging to the graphene family and MSCs during the wound healing process. In addition, this study discusses the cytocompatibility of graphene, its uses as a platfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 171 publications
(298 reference statements)
1
30
0
Order By: Relevance
“…Currently, mesenchymal stem cells (MSCs) are widely reported to involve many pathophysiological processes [12][13][14] and have a curative effect in treating various diseases [15][16][17]. MSCs, which can differentiate into epidermal cells and skin appendages (sebaceous 1and sweat glands), can be isolated and amplified from the umbilical cord, bone marrow, fat, and other tissues and have recently been reported to decrease burn the wound area in rats and mice [14,18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, mesenchymal stem cells (MSCs) are widely reported to involve many pathophysiological processes [12][13][14] and have a curative effect in treating various diseases [15][16][17]. MSCs, which can differentiate into epidermal cells and skin appendages (sebaceous 1and sweat glands), can be isolated and amplified from the umbilical cord, bone marrow, fat, and other tissues and have recently been reported to decrease burn the wound area in rats and mice [14,18].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, mesenchymal stem cells (MSCs) are widely reported to involve many pathophysiological processes [ 12 – 14 ] and have a curative effect in treating various diseases [ 15 – 17 ]. MSCs, which can differentiate into epidermal cells and skin appendages (sebaceous 1and sweat glands), can be isolated and amplified from the umbilical cord, bone marrow, fat, and other tissues and have recently been reported to decrease burn the wound area in rats and mice [ 14 , 18 ]. Despite the multipotency of stem cells, an increasing number of studies have shown that the efficacy of MSCs primarily depends on the secretion of a variety of factors, such as vascular endothelial growth factor (VEGF), epidermal growth factor (EGF), fibroblast growth factor (FGF), insulin-like growth factor (IGF), platelet-derived factor growth factor (PDGF), transforming growth factor beta (TGF beta), IL-4, IL-6, and IL-10, which play an important role in angiogenesis, cell recruitment, immune regulation, and wound healing, rather than the stemness of cells [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…The expression of fak increased in HS-5 and HepG2 cultivated on GO with CELE supplementation. GO may reduce [41,51] or enhance fak expression [52], which may depend on the presence of ligands, and consequently in our research, CELE was added to prevent this. Liver cells are anchor-dependent cells in which the level of fak increases in suspension culture [53,54,55].…”
Section: Discussionmentioning
confidence: 94%
“…The expression of fak increased in HS-5 and HepG2 cultivated on GO with CELE supplementation. GO may reduceZhu et al 2017) or enhance fak expression(Lasocka et al 2019), which may depend on the presence of ligands, and consequently in our research, CELE was added to prevent this. Liver cells are anchor-dependent cells in which the level of fak increases in suspension culture(Cance et al 2000;Shang et al 2019;Ren et al 2015).…”
mentioning
confidence: 93%